2010
DOI: 10.1002/mnfr.201000414
|View full text |Cite
|
Sign up to set email alerts
|

Potential health‐promoting effects of astaxanthin: A high‐value carotenoid mostly from microalgae

Abstract: The ketocarotenoid astaxanthin can be found in the microalgae Haematococcus pluvialis, Chlorella zofingiensis, and Chlorococcum sp., and the red yeast Phaffia rhodozyma. The microalga H. pluvialis has the highest capacity to accumulate astaxanthin up to 4-5% of cell dry weight. Astaxanthin has been attributed with extraordinary potential for protecting the organism against a wide range of diseases, and has considerable potential and promising applications in human health. Numerous studies have shown that astax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
329
1
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(351 citation statements)
references
References 122 publications
2
329
1
19
Order By: Relevance
“…In addition to avoidance of carcinogenic agents, regular intake of chemopreventive compounds is a promising approach for reducing cancer incidence. A number of substances naturally occurring in foodstuffs, particularly antioxidant compounds in plant products, have shown promise as potential chemopreventive agents [17] . Among these phytonutrients, the yellow, orange and red carotenoid pigments have recently sparked much interest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to avoidance of carcinogenic agents, regular intake of chemopreventive compounds is a promising approach for reducing cancer incidence. A number of substances naturally occurring in foodstuffs, particularly antioxidant compounds in plant products, have shown promise as potential chemopreventive agents [17] . Among these phytonutrients, the yellow, orange and red carotenoid pigments have recently sparked much interest.…”
Section: Discussionmentioning
confidence: 99%
“…salmon, trout, red sea bream, shrimp, lobster etc. Several studies revealed the beneficial health effect of AX as photoprotectants, eye health, antiinflammatory, improvement of immunity and other important application in nutraceuticals, cosmetics, food and feed industries (Yuan et al, 2011;Ciapara et al, 2006;Guerin et al, 2003). Due to its various health beneficial properties, commercially natural AX is cultivated from Haematococcus Pluvialis (richest source), which can accumulate higher amount of astaxanthin under stressful conditions (Wayama et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It also exhibits anti-infl ammatory and immunostimulatory action [Goswami et al 2010, Pashkow et al 2008, Yuan et al 2011. The benefi cial effect of astaxanthin is related to the presence of coupled double bonds in the long hydrocarbon chain as well as polar hydroxyl and carbonyl groups in both ionone rings [Liu and Osawa 2007].…”
Section: Introductionmentioning
confidence: 99%